THU0701 Updated incidence and costs of hip fractures in elderly italian population. (12th June 2018) - Piscitelli, P.; Feola, M.; Neglia, C.; Rao, C.; Rizzo, E.; Tarantino, U.
Abstract : Background: It had already been evaluated the hospitalisation rate of femoral neck fractures in the elderly Italian population over ten years, showing that incidence of hip fractures in Italy are continuously increasing, although women aged 65–74 years old started showing a decreasing trend. Objectives: To update our previous researches about the burden of hip fractures in elderly Italian population. Methods: We analysed national hospitalizations records from 2007 to 2014 to compute age- and sex-specific standardised rates. Results: 7 41 633 hospitalizations were observed in people≥65 (women: 568, 203; men: 173, 430), with an overall increase of 5.50% over the 8 year period (females:+3.36; males:+12.9%). About 43.75% of total hip fractures were suffered by patients aged ≥85 years old. Women aged ≥85 accounted for 34.49% (n=255, 763) of total fractures. The incidence rate per 10 000 inhabitants in people aged 65–74 decreased from 28.65 to 25.31 in women (–13.02%) and from 13.41 to 11.65 in men (–13.12%). Incidence per 10 000 in people 75–84 decreased from 121, 6 to 105, 2 in women (−13.49%) and from 55.8 to 47.5 in men (–14.87%). Paradoxally, also in people aged ≥85, the incidence per 10 000 declined from 300.99 to 268.72 in women (–10.72%) and from 174.59 to 171.17 in men (−1.96%) because the number of subjects aged ≥85 is growing faster than the number of fractures occurring in this latter age group. Direct hospitalisation costs and rehabilitation costs increased from 433 to 457 million Euros and from 478 to 504 million Euros over the 8 year period, respectively. Overall costs of hip fractures in people aged ≥65 years old raised from 911 to 961 million Euros from 2007 to 2014. Conclusions: The number of hip fractures and related hospitalizations costs in Italian elderly population is still increasing due to the fractures occurring in people≥85 years old, although incidence rates are decreasing in all the age groups. Reference: [1] Ten years of hip fractures in Italy: For the first time a decreasing trend in elderly women. Piscitelli P, Feola M, Rao C, Celi M, Gasbarra E, Neglia C, Quarta G, Liuni FM, Parri S, Iolascon G, Brandi ML, Distante A, Tarantino U. World J Orthop2014Jul 18;5(3):386–91. doi:10.5312/wjo.v5.i3.386 Disclosure of Interest: None declared